Associations between use of psychotropic medications and use of hormonal contraception among girls and women aged 15–49 years in Finland: a nationwide, register-based, matched case–control study. Issue 2 (22nd February 2022) - Toffol, Elena; Partonen, Timo; Heikinheimo, Oskari; But, Anna; Latvala, Antti; Haukka, Jari
Abstract : Objectives: The relationship between the use of contraception and of psychiatric medications is understudied. We examined whether the current and past use of psychotropic medications is associated with the use and type of hormonal contraception (HC). Design: Nationwide register-based matched case–control study. Settings: All fertile-aged (15–49 years) girls and women living in Finland in 2017; data from several national registers. Participants: 294 356 girls and women with a redeemed prescription of HC in 2017, and their same-sized control group of non-users (n=294 356) identified through the Prescription Centre. Main outcome measures: Associations between the use of psychotropic medications and the use of HC, and the type of HC tested in logistic regression models. Results: Altogether 19.5% of the HC users, and 18% of the HC non-users received at least one prescription for a psychotropic medication in 2017. Among HC users, the proportions of occasional and regular users of psychotropic medications in 2013–2016 were 4.5% and 14.8%, while among HC non-users the respective figures were 4.3% and 14.6%, respectively. In multivariable logistic regression models both the use of psychotropic medications in 2017, and their occasional or regular use between 2013–2016 were associated with higher odds of HC use, although with small to very small effect sizes (ORs between 1.37 and 1.06 and 95% CIs 1.22 to 1.53, and 1.03 to 1.09, respectively). After adjustment for covariates, when fixed combinations of progestogens and oestrogens for systemic use was the reference category, women using almost any class of psychotropic medications had higher odds of using other types of HC. Conclusions: Fertile-aged girls and women with current and past use of psychotropic medications have higher odds of using HC, with a specific pattern in the type of contraceptives used. Further research is warranted to examine whether our observations indicate a reduction of unwanted pregnancies in women with psychiatric disorders.